Critical thinking and problem-solving: from higher education to professional contexts - Braga, Inês (2019)
The critical thinking is a mental process that requires analysis and evaluation of information. It’s a very important skill, mentioned in several international Standards of Information Literacy and in important documents on Education, published by organizations of reference like UNESCO or Associations very recognized of the areas of Libraries, Technologies and Education. It’s a key competency of the 21st century, included in the well-known 4 Cs: Communication, Collaboration, Creativity and Critical Thinking and it’s interrelated with other competencies. In fact, critical thinking is often associated with problem-solving and decision making, and it’s considered to be fundamental to the academic, professional and social success of individuals, living in the information society. According to the complexity of a global world in which new information and communication technologies abound, it’s essential to train citizens to adopt reflective and critical attitudes about the many information products whose quality is often doubtful or inadequate for the informational needs of the individual. Given the information overload, especially on digital platforms, it’s crucial that information users be taught to search for information, select, use and communicate credible information in an ethical manner. So, because such skills are not innate, they need to be taught, whether in formal or informal contexts of learning. The researcher, also a teacher of higher education, motivated by the results of earlier research carried out in Portuguese polytechnical higher education on the development of information literacy skills, intends to deepen issues related to the critical thinking, crucial for the global formation of the human being and for the success of organizations. The purpose of this research is to reflect on how the teaching system - especially higher education - values and teaches to develop this essential competence for the integration and success of those who are in an academic process training and who will later have to demonstrate it in the professional reality, since that skill is one of the most required by the labour market. The methodology adopted is based on a theoretical approach to the theme - through the literature review - and the sharing of experience in the way the teacher has adopted some pedagogical strategies that she considers appropriate to the development of this skill. The results of the research are the theoretical and practical analysis of good pedagogical practices. Also, the elaboration of a set of questions to reflect on the relevance and added value that the critical thinking can bring in the decision-making process - whether in the academic world or in the professional world, can inspire new approaches and improvements. It is concluded that the pedagogical approach on the subject under study is complex and that the most successful cases will result from collaborative work by the various educational agents involved. It highlights the importance of the Ministries of Education and their teaching policies, the directions of schools, teachers, students and employers. There should be a general awareness of the importance of developing this skill in the educational community, greater visibility of its presence in curricula, effective and systematic teaching along the academic path (betting on early education) and institutional support and commitment indispensable for its consolidation.